Respon empat klon harapan ubikayu terhadap pupuk anorganik di lahan kering tanah alfisol=The response of five promisisng cassava clones to inorganic fertilizer in upland alfisol. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Four promising cassava clones had been evaluated in Alfisol upland in Gunungkidul, Yogyakarta from October 1997 up to August 2000 and in Malang East Java from October 1999 up to August 2000. The objective was to evaluate the adaptability and productivity of the clones grown in Alfisol upland and its response to N, P, K, and S fertilizers. The 1997/1998 experiment used randomized complete block design with four replications. The treatments were five clones of cassava that managed with optimum inputs. The experiment in 1998/1999 laid in factorial randomized complete block design were replicated three times. There were twelve treatments of combinations of N, P, K and S fertilizer which applied to four promising clones (KTKN, OMM-90-2-66, OMM-90-3-76 and OMM-90-7-74) and a check variety (Adira-1). The experiment in 1999/2000 was arranged in factorial randomized complete block design with three replications. The treatments consist of five cassava clones and three dosages of ZA fertilizer (0, 50 and 100 kg ZA/ha). Plants were planted in double row system with plant spacing of (50, 160) cm x 100 cm. All plants were fertilized with 90 kg N/ha (from Urea and ZA) + 100 kg SP36/ha + 100 kg KC1/ha. The results showed that clone OMM-90-7-74 was consistently produced high tuber's yield in Alfisol upland, and therefore this clone is considered adaptive as in Alfisol upland. Tuber's yield of OMM-90-7-74 was 68% higher than Adira-1 ' and prospective for substituting it. Tuber yields of OMM-90-3-76 and KTKN were lower than clone OMM-90-7-74 but were higher than Adira-1 Clone OMM-90-7-74, OMM-90-3-76 and KTKN were responsive to NPS fertilization but did not respond to K fertilization. Application of farmyard manure for cassava in Alfisol upland was very demanded for producing optimum yield. Application of 100 kg ZA/ha in Alfisol in which soil pH more than 6.5 increased P and S nutrients uptake (16% and 85%, respectively) and increased the tuber's yield (45%). Alfisol soil with soil pH less than 6 will increase only S nutrient uptake (204%) and tuber yield (49%).